Understanding barriers to stool adequacy: results from a programmatic assessment of Pakistan's acute flaccid paralysis active surveillance system in 12 priority districts - Keri Geiger; Abul Aziz; Chukwuma Mbaeyi; Zainul Abedin Khan; Mohammed Soghaier; Aimee Summers (Frontiers in Public Health)
IntroductionPakistan's acute flaccid paralysis (AFP) surveillance system is an essential part of efforts to eradicate poliomyelitis, as Pakistan and Afghanistan are the only countries where wild poliovirus remains endemic. The two primary performance indicators for AFP surveillance are the non-polio AFP rate for children aged <15 years and stool adequacy, defined as the percentage of AFP cases for which two timely stool samples arrive at the laboratory in good condition. Despite consistently meeting targets for both indicators at the national level, some districts in Pakistan failed to meet the stool adequacy target of ≥80% in 2023 or had declining stool adequacy. In March 2024, we assessed AFP surveillance in 12 districts in Pakistan with low stool adequacy to characterize barriers to meeting the target.MethodsThe assessment included review of case investigation forms from AFP cases with patient paralysis onset during January 2023–mid-March 2024 with inadequate stool samples, as well as visits to health facilities serving as active surveillance sites and interviews with surveillance and laboratory personnel.ResultsThe most common barrier to stool adequacy was a delay between onset of paralysis and AFP case notification, which occurred in 111 of 158 (70%) inadequately sampled AFP cases reviewed. This delay was most frequently attributed to missed reporting by healthcare facilities, caretakers seeking healthcare many days after paralysis onset, or a combination of both. Additionally, only 63% of health facilities showed adequate active surveillance visit compliance.DiscussionThe assessment exposed gaps in AFP surveillance knowledge for some health facility staff, especially nurses and other paramedical or support professionals. Recommendations to improve the AFP surveillance system include monitoring and encouraging compliance with systematically scheduled health facility visits, increasing the frequency of AFP surveillance orientations, including paramedical professionals in AFP surveillance training, and developing a comprehensive messaging plan to increase knowledge about prompt reporting of AFP among healthcare providers and the public.